The effectiveness of treadmill and swimming exercise in an animal model of osteoarthritis - da Silva, Leandro Almeida; Thirupathi, Anand; Colares, Mateus Cardoso; Haupenthal, Daniela Pacheco dos Santos; Venturini, Ligia Milanez; Corrêa, Maria Eduarda Anastácio Borges; Silveira, Gustavo de Bem; Haupenthal, Alessandro; do Bomfim, Fernando Russo Costa; de Andrade, Thiago Antônio Moretti; Gu, Yaodong; Silveira, Paulo Cesar Lock (Frontiers in Physiology, 2023)
Osteoarthritis (OA) is considered an inflammatory and degenerative joint disease, characterized by loss of hyaline joint cartilage and adjacent bone remodeling with the formation of osteophytes, accompanied by various degrees of functional limitation and reduction in the quality of life of individuals. The objective of this work was to investigate the effects of treatment with physical exercise on the treadmill and swimming in an animal model of osteoarthritis. Forty-eight male Wistar rats were divided (n=12 per group): Sham (S); Osteoarthritis (OA); Osteoarthritis + Treadmill (OA + T); Osteoarthritis + Swimming (OA + S). The mechanical model of OA was induced by median meniscectomy. Thirty days later, the animals started the physical exercise protocols. Both protocols were performed at moderate intensity. Forty-eight hours after the end of the exercise protocols, all animals were anesthetized and euthanized for histological, molecular, and biochemical parameters analysis. Results showed that physical exercise performed on a treadmill was more effective in attenuating the action of pro-inflammatory cytokines (IFN-γ, TNF-α, IL1-β, and IL6) and positively regulating anti-inflammatories such as IL4, IL10, and TGF-β in relation to other groups. In addition to maintaining a more balanced oxi-reductive environment within the joint, treadmill exercise provided a more satisfactory morphological outcome regarding the number of chondrocytes in the histological evaluation. As an outcome, better results were found in groups submitted to exercise, mostly treadmill exercise.